2024
DOI: 10.1186/s12915-024-01854-9
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated adaptative genetic architecture and language-related demographical history in South China inferred from 619 genomes from 56 populations

Qiuxia Sun,
Mengge Wang,
Tao Lu
et al.

Abstract: Background The underrepresentation of human genomic resources from Southern Chinese populations limited their health equality in the precision medicine era and complete understanding of their genetic formation, admixture, and adaptive features. Besides, linguistical and genetic evidence supported the controversial hypothesis of their origin processes. One hotspot case was from the Chinese Guangxi Pinghua Han people (GPH), whose language was significantly similar to Southern Chinese dialects but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 93 publications
(125 reference statements)
0
0
0
Order By: Relevance
“…Recent studies utilizing ancient genomic resources have revealed that human expansion from regions such as the Mongolia Plateau, Amur River Basin, Yellow River Basin, Yangtze River Basin, and the Eurasian Steppe has gradually facilitated complex patterns of population structure and genetic diversity in East Asia [ 5 – 8 ]. Evolutionary reconstructions among ethnolinguistically modern populations suggest that differentiated selective pressures and admixture landscapes have enriched the complexity of the population history and biological adaptations of East Asians [ 6 , 9 12 ]. Yang et al identified genomic substructures between ancient northern East Asians (ANEAs) and ancient southern East Asians (ASEAs).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies utilizing ancient genomic resources have revealed that human expansion from regions such as the Mongolia Plateau, Amur River Basin, Yellow River Basin, Yangtze River Basin, and the Eurasian Steppe has gradually facilitated complex patterns of population structure and genetic diversity in East Asia [ 5 – 8 ]. Evolutionary reconstructions among ethnolinguistically modern populations suggest that differentiated selective pressures and admixture landscapes have enriched the complexity of the population history and biological adaptations of East Asians [ 6 , 9 12 ]. Yang et al identified genomic substructures between ancient northern East Asians (ANEAs) and ancient southern East Asians (ASEAs).…”
Section: Introductionmentioning
confidence: 99%
“…However, the current focus of large-scale genetic research on European populations is limiting our understanding ( Bick et al, 2024 ). The underrepresentation of non-European populations in these studies not only hampers the development of disease risk models but also prevents us from fully capturing the vast spectrum of human genetic diversity ( Sun et al, 2023 ; He et al, 2024 ; Li et al, 2024 ; Sun et al, 2024 ). This is because demographic history, linkage disequilibrium, and adaptive evolutionary histories vary significantly across different continental groups.…”
Section: Introductionmentioning
confidence: 99%